THE ASSESSMENT OF PEDESTRIAN FOOTBRIDGE USAGE IN MALAYSIA: THE CASE OF IPOH CITY - HASAN, RAZI AZIZ (2015)
The number of annually registered vehicles in Malaysia keeps increasing at about 6% per annum, and this will be accompanied by the increase of potential risk in the congested streets where some pedestrians will suffer from the threats of dangerous accidents. From this point, providing footbridges will be the best solution to avoid such type of risk, by separating pedestriansfrom vehicular traffic, and securing a safe path for pedestrians with no chance of collision with vehicles. In spite of these characteristics that secure absolute safety, this structure suffers from non-optimal performance resulting from non-compliance with the pedestrians to use the bridge. This researchaims to determine the most effective factors that affect the pedestrians' decision whether to utilize the footbridge or to cross on the street level. Thirteen factors were investigated by using the questionnaire, and the relative importance index method was used to determine the ranking of these factors.